Pengaruh Family Ownership dan Likuiditas pada Agresivitas Pajak dengan Corporate Governance sebagai Variabel Pemoderasi - Puspadewi, Putu Nanda; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 35 No 1 (2025), 2025)
This study aims to obtain empirical evidence regarding the effect of family ownership and liquidity on tax aggressiveness with corporate governance as a moderating variable. The sample of this study amounted to 20 companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The analysis technique used is Moderated Regression Analysis (MRA). The results of this study indicate that family ownership has a negative effect on tax aggressiveness and liquidity has no effect on tax aggressiveness. This study also shows that corporate governance is able to strengthen the effect of family ownership on tax aggressiveness but cannot moderate the effect of liquidity on tax aggressiveness. Keywords: Tax aggressiveness; Family Ownership; Liquidity; Corporate Governance